Algorithms for sensor systems : 8th International Symposium on Algorithms for Sensor Systems, Wireless Ad Hoc Networks and Autonomous Mobile Entities, ALGOSENSORS 2012, Ljubljana, Slovenia, September 13-14, 2012. Revised Selected Papers - Halldorsson, Magnus M.; Bar-Noy, Amotz (Lecture Notes in Computer Science, 2013)
This book constitutes the thoroughly refereed post-conference proceedings of the 8th International Workshop on Algorithms for Sensor Systems, Wireless Ad Hoc Networks, and Autonomous Mobile Entities, ALGOSENSORS 2012, held in Ljubljana, Slovenia, in September 2012. The 11 revised full papers presented together with two invited keynote talks and two brief announcements were carefully reviewed and selected from 24 submissions. The papers are organized in two tracks: sensor networks - covering topics such as barrier resilience, localization, connectivity with directional antennas, broadcast scheduling, and data aggregation; and ad hoc wireless and mobile systems - covering topics such as: SINR model; geometric routing; cognitive radio networks; video delivery; and mapping polygons.